PENGARUH PENGGUNAAN TEKNOLOGI AUGMENTED REALITY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PERKEMBANGBIAKAN MAKHLUK HIDUP - Nazliyati, Nazliyati; Danil, M. Danil; Aldyza, Nadia (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
AbstractAugmented Reality (AR) technology can enhance learning by visualizing abstract concepts, such as complex science materials, and enriching students' learning experiences. At UPTD SD Negeri 27 Peusangan, the application of AR is expected to help students understand the reproduction of living things interactively and interestingly, considering the low critical thinking skills in conventional learning. Experimental research with the One Group Pretest-Posttest design showed that the use of AR improved students' critical thinking skills, with an increase percentage of 64.9%. The results of the study conducted at SD Negeri 27 Peusangan, the use of Augmented Reality technology in learning the reproduction of living things material showed quite good results. This can be seen from the pretest and posttest data which showed students' enthusiasm in learning and an increase in critical thinking skills in each indicator. In addition, it was also found that the use of Augmented Reality technology has an influence on increasing critical thinking skills with a percentage of 64.9%. This study involved 13 grade students. Keywords: augmented reality, critical thinking, reproduction of living things